2021
DOI: 10.1111/vox.13065
|View full text |Cite
|
Sign up to set email alerts
|

The risk to future pregnancies of transfusing Rh(D)‐negative females of childbearing potential with Rh(D)‐positive red blood cells during trauma resuscitation is dependent on their age at transfusion

Abstract: Background A risk assessment model for predicting the risk of haemolytic disease of the fetus and newborn (HDFN) in future pregnancies following the transfusion of Rh(D)‐positive red blood cell (RBC)‐containing products to females of childbearing potential (FCP) was developed, accounting for the age that the FCP is transfused in various countries. Methods The HDFN risk prediction model included the following inputs: risk of FCP death in trauma, Rh(D) alloimmunization rate following Rh(D)‐positive RBC transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…It is interesting that 51% of the centers that use LTOWB would administer RhD‐positive LTOWB to females of childbearing potential whose RhD‐type is either negative or unknown at the time of the transfusion. Perhaps this reflects the adoption of the findings of studies that demonstrated a survival benefit when blood products were administered early in the resuscitation, 6–9 that there are emerging data showing some benefits of transfusing LTOWB, 21–24 and a recognition that hemolytic disease of the fetus and newborn, while still a stressful and emotionally draining diagnosis, is now largely a manageable condition in many parts of the world 25–28 …”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that 51% of the centers that use LTOWB would administer RhD‐positive LTOWB to females of childbearing potential whose RhD‐type is either negative or unknown at the time of the transfusion. Perhaps this reflects the adoption of the findings of studies that demonstrated a survival benefit when blood products were administered early in the resuscitation, 6–9 that there are emerging data showing some benefits of transfusing LTOWB, 21–24 and a recognition that hemolytic disease of the fetus and newborn, while still a stressful and emotionally draining diagnosis, is now largely a manageable condition in many parts of the world 25–28 …”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one reason for this higher rate is the lower median age of the RhD‐negative recipients in this study (41 years) compared to the recipient ages in the other studies, which ranged from approximately 59 to 74 years 6–9 . In spite of this higher alloimmunization rate, when considering all of the factors that have to combine in order for an RhD‐negative FCP who received RhD‐positive primary RBC‐containing blood products during her trauma resuscitation to have a future fetus die from HDFN, this higher RhD alloimmunization rate changes the calculated average rate of intrauterine fetal demise (IUFD) due to anti‐RhD mediated HDFN from 0.3% to 0.6% using one published risk assessment model 19 and the risk of severe HDFN/ IUFD in an 18‐year old FCP in the USA from 1.8% to 2.7% in another age‐dependent risk assessment model 20 . Models that attempt to quantify the risk of HDFN associated with transfusion of RhD‐positive RBC‐containing products to RhD‐negative FCP should account for the more age‐appropriate RhD‐alloimmunization rate of 34.9% to arrive at more accurate HDFN risk estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of future fetal or newborn death or severe neurologic morbidity occurring due to an exposure to emergently transfused Rh + whole blood is estimated to be approximately 0.3% in all women, 27 and 3.4% in women 18 years of age or younger. 28 Given that the risk of mortality in children from severe hemorrhage is 36%-50%, 2,3 and the reduction in mortality in both pediatric and adult studies ranges from 20% to 50%, the risk of death from hemorrhage may out-weigh the potential risk of D-alloimmunization. However, in developing parameters for an RCT of emergency use of LTOWB, it is clear from these results that this aspect of the trial must be resolved prior to initiating a trial of LTOWB in this population.…”
Section: Discussionmentioning
confidence: 99%